Hexokinase 1 is required for glucose-induced repression of bZIP63, At5g22920, and BT2 in Arabidopsis - Kunz, Sabine; Gardeström, Per; Pesquet, Edouard; Kleczkowski, Leszek A. (Frontiers in Plant Science, 2015)
Simple sugars, like glucose and sucrose, act as signals to modulate the expression of hundreds of genes in plants. Frequently, however, it remains unclear whether this regulation is induced by the sugars themselves or by their derivatives generated in the course of carbohydrate (CH) metabolism. In the present study, we tested the relevance of different CH metabolism and allocation pathways affecting expression patterns of five selected sugar-responsive genes (bZIP63, At5g22920, BT2, MGD2 and TPS9) in Arabidopsis thaliana. In general, the expression followed diurnal changes in the overall sugar availability. However, under steady growth conditions, this response was hardly impaired in the mutants for CH metabolizing/ transporting proteins (adg1, sex1, sus1-4, sus5/6 and tpt2), including also hexokinase1 (HXK1) loss- and gain-of-function plants - gin2.1 and oe3.2, respectively. In addition, transgenic plants carrying pbZIP63::GUS showed no changes in reporter-gene-expression when grown on sugar under steady-state conditions. In contrast, short-term treatments of agar-grown seedlings with 1% glucose or sucrose induced pbZIP63::GUS repression, which became even more apparent in seedlings grown in liquid media. Subsequent analyses of liquid-grown gin2.1 and oe3.2 seedlings revealed that glucose-dependent regulation of the five selected genes was not affected in gin2.1, whereas it was enhanced in oe3.2 plants for bZIP63, At5g22920 and BT2. The sugar treatments had no effect on ATP/ADP ratio, suggesting that changes in gene expression were not linked to cellular energy status. Overall, the data suggest that HXK1 does not act as glucose sensor controlling bZIP63, At5g22920 and BT2 expression, but it is nevertheless required for production of a downstream metabolic signal regulating their expression.